Asymmetrical lymphoid and myeloid lineage commitment in multipotent hematopoietic progenitors - Lai, Anne Y. (The Rockefeller University Press, 2006)
The mechanism of lineage commitment from hematopoietic stem cells (HSCs) is not well understood. Although commitment to either the lymphoid or the myeloid lineage is popularly viewed as the first step of lineage restriction from HSCs, this model of hematopoietic differentiation has recently been challenged. The previous identification of multipotent progenitors (MPPs) that can produce lymphocytes and granulocyte/macrophages (GMs) but lacks erythroid differentiation ability suggests the existence of an alternative HSC differentiation program. Contribution to different hematopoietic lineages by these MPPs under physiological conditions, however, has not been carefully examined. In this study, we performed a refined characterization of MPPs by subfractionating three distinct subsets based on Flt3 and vascular cell adhesion molecule 1 expression. These MPP subsets differ in their ability to give rise to erythroid and GM lineage cells but are equally potent in lymphoid lineage differentiation in vivo. The developmental hierarchy of these MPP subsets demonstrates the sequential loss of erythroid and then GM differentiation potential during early hematopoiesis. Our results suggest that the first step of lineage commitment from HSCs is not simply a selection between the lymphoid and the myeloid lineage.